2020
DOI: 10.1101/2020.05.17.100560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-Related Colonic Mucosal Microbiome Community Shifts in Monkeys

Abstract: Recent evidence suggests that gut microbiome changes that occur with age impact the health of the host. While it is known that the gut microbiome and physiological systems interact, the relationship between the microbiome in an aged body system remains to be clearly defined, particularly in the context of inflammation. Therefore, we aimed to evaluate systemic inflammation and the mucosal microbiome in young and old female vervet monkeys. Ascending colon mucosal biopsies and blood samples from healthy young and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Vervets, like humans, exhibit increasing intestinal dysfunction with age (Mitchell et al, 2017). Compared to younger adults, old adults have a lower Firmicutes:Bacteroidetes ratio (Figure 6c), like elder humans, and a lower abundance of butyrate‐producing microbes, consistent with less healthy profiles (Vemuri et al, 2020). Like humans, old vervets have reduced gait speed and sarcopenia.…”
Section: Aging‐related Physical Declinementioning
confidence: 65%
See 1 more Smart Citation
“…Vervets, like humans, exhibit increasing intestinal dysfunction with age (Mitchell et al, 2017). Compared to younger adults, old adults have a lower Firmicutes:Bacteroidetes ratio (Figure 6c), like elder humans, and a lower abundance of butyrate‐producing microbes, consistent with less healthy profiles (Vemuri et al, 2020). Like humans, old vervets have reduced gait speed and sarcopenia.…”
Section: Aging‐related Physical Declinementioning
confidence: 65%
“…Walking speed was calculated as distance/time. (c) Older adult vervets had a lower Firmicutes:Bacteroidetes ratio than did younger adults ( p = .03) (adapted from Vemuri et al, 2020). (d) Two examples from the Wake Forest Maze Task of executive function; examples of an easy (left) maze and difficult (right) maze.…”
Section: The Evidence For An Age‐related Vervet Model Of Late Onset Alzheimer's Diseasementioning
confidence: 99%
“…1,2 A compromised gut barrier makes the gut mucosal lining "leaky", enabling the translocation of microbes or microbial products into the systemic circulation from the gut lumen in a process known as microbial translocation (MT), leading to systemic low-grade endotoxemia and inflammation. [3][4][5] Further, studies have shown that a defective gut barrier alters the composition of the microbes residing in the gut (gut microbiome), resulting in dysbiosis, which worsens overall health. 1,3,[6][7][8][9] Therefore, it is essential to comprehend regulators of the gut barrier and gut microbiome-related changes to help prevent the onset of various chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the microbiome result from factors such as aging, environment, diet, activity and other influences, and so looking at the gut microbiome at a number of time points is imperative to capture the true effects. 4,5,9 Due to rapid shifts in the gut microbiome composition and to assess whether the gut barrier and gut microbiota are linked to hypertension, more longitudinal studies are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation